PEMBUATAN MIKROKRISTALIN SELULOSA (MCC) dari BATANG PISANG MAS (Musa acuminata colla) dengan AVICEL PH 102 SEBAGAI PEMBANDING TAHUN 2019 - Erdiwan Erdiwan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Commercial cellulose microcrystalline known as Avicel PH 102, which is a tablet filling material Avicel PH 102 which is expensive and uses a lot of it, it is necessary to look for other alternative sources of producing microcrystalline cellulose. The Waste of banana stem contains water content of 80-90%, cellulose 63-64%, hemicellulose 20%, and lignin 5% and contains 11-12% other constituens so that it can be the basic material for making MCC. This study aimed to isolate α-cellulose from banana mas stems and characterize microcrystalline cellulose with Avicel PH 102. The method of this study was an experimental. Microcrystalline banana stem cellulose is obtained by heating banana stem powder with 4% NaOH which serves to dissolve lignin, then bleached with 2.5% NaOCl, 17.5% NaOH heated to dissolve β-cellulose and γ-cellulose, and heated with HCL 2 N . The results are hydrolyzed with α-cellulose and then hydrolyzed with 2.5N HCl to give microcrystalline cellulose, which is characterized and compared to Avicel PH102. The result of characterization of banana mas stem microcrystalline cellulose and Avicel PH 102 which were obtained respectively is organoleptic tests of coarse powder, white, doesn’t have any smells; pH 6.6 and 6.5; solubility of substances in water 0.023 and 0.023%; total ash content are 0.17 and 0.12%; decrease of drying 5.47 and 5.28%; real density 0.337 and 0.404 g / cm3; true type weight 1.43 and 1.43 g / cm3; incompressible density 0.478 and 0.480 g / cm3; compressibility index 41.77 and 18.85%; Hausner index 1.41 and 1.18; porosity; 76.43 and 93.640%. Based on the results of the study concluded that microcrystalline cellulose can be made from banana mas stems and has the same characteristics as Avicel PH 102.